In Vitro and In Silico Assessment of Methanol Extract from Moringa oleifera Seeds as α-Amylase Inhibitor - Natsir, Hasnah; A Arfah, Rugaiyah; Arif, Abdur Rahman; Nadir, Muhammad; Anita, Anita; Sartika, Sartika; Rahmi, Nur; Karimah, Aulia (Indonesian Journal of Chemical Research, 2024)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia, posing a global health threat. Current diabetes treatments often rely on synthetic drugs with side effects, prompting the search for safer natural alternatives. This study investigated the secondary metabolic compounds in methanol extract from M. oleifera seeds and evaluated their antidiabetic activity. The α-amylase enzyme was analyzed to determine optimal incubation time, pH, and temperature. The antidiabetic activity was assessed via α-amylase inhibition using in vitro and in silico methods. Phytochemical screening revealed the presence of flavonoids, alkaloids, and tannins in the extract. Optimal enzyme conditions were 30 minutes of incubation, pH 6.9, and 25 °C. The extract showed the highest activity at 15% concentration with 67.94% inhibition and an IC50 of 15.38%, compared to acarbose with 41.76% inhibition and an IC50 of 17.89%. In silico analysis indicated that 9-octadecanoic acid (Z) methyl ester had a lower inhibition constant and binding energy (2.67 mM and -3.51 kcal/mol) than acarbose (15.72 mM and -2.46 kcal/mol), suggesting a higher enzyme affinity. These findings suggest that M. oleifera seeds contain compounds with potential as antidiabetic agents.